Pathogenicity of phylogenetic species in the Fusarium graminearum complex on soybean seedlings in Argentina - Barros, Germán Gustavo (2014)
Soybean (Glycine max L.) is one of the main crops in Argentina. Most of the studies of pathogenicity in the Fusarium graminearum complex have focused on strains isolated from wheat and maize, and there is little information on strains isolated from soybean. Our objective in the present study was to compare the pathogenicity among soybean isolates of different phylogenetic species within the Fusarium graminearum complex on soybean seedlings under controlled conditions. Six strains representing three different phylogenetic species (F. graminearum, F. meridionale and F. cortaderiae) were identified by partial sequencing of the Translation Elongation Factor -1α gene (TEF-1) and evaluated for pathogenicity. All six strains reduced emergence, mainly by causing pre-emergence damping-off, seedling height and root dry weight and produced abnormal seedlings. The mean disease severity averaged across all isolates was approximately 3.0 in a 0–4 rating scale where 0 = healthy seedling and 4 = dead seedling. Significant differences in pathogenicity were observed among F. graminearum, F. meridionale and F. cortaderiae. These results are consistent with the hypothesis that different phylogenetic species within the Fusarium graminearum complex isolated from soybean are pathogenic under controlled conditions to soybean seedlings in Argentina. The present study demonstrates for the first time the pathogenic effect of F. meridionale on soybean in Argentina.